97.4k views
5 votes
PLEASE HELP ASAP 30 PTS

PLEASE HELP ASAP 30 PTS-example-1
User DavGin
by
6.1k points

1 Answer

3 votes

Answer:

c (2,3,-2)

Explanation:

3x+y+z = 7

x+3y-z =13

y = 2x-1

Add the first two equations together to eliminate z

3x+y+z = 7

x+3y-z =13

----------------------

4x+4y = 20

Divide by 4

4x/4 + 4y/4 = 20/4

x+y = 5

We know y = 2x-1. substitute this into the equation

x+ (2x-1) = 5

Combine like terms

3x-1 =5

Add 1 to each side

3x-1+1 =5+1

3x=6

Divide by 3

3x/3 = 6/3

x=2

Now we can find y

y = 2x-1

y = 2(2)-1

y =4-1

y= 3

We know x and y, now we need to find z

3x+y+z = 7

3(2) +3 +z = 7

6+3+z =7

9+z=7

Subtract 9 from each side

(-9+z =7-9

z=-2

So x=2,y=3 =-2

(2,3,-2)

User Rmpestano
by
5.5k points